(untitled) (LACCEI, 2024)
The community of Agua Caliente located in the municipality of Puerto Cortés is cut off when high intensity rainfall occurs in the area. Therefore, it is necessary to geometrically and structurally design a bridge that allows continuous vehicular access. An initiative is proposed to solve this problem, through a hydrological study to know the characteristics of the micro-basin, carrying out a rainfall simulation through a program, where the following data were obtained, such as the flow of 23.8 m^3/s, the extraordinary maximum water level of 100.28 meters above sea level, as well as providing the study of the soil to determine the mechanical properties in the vicinity of the river. All of the above, in order to analyze the data collection to carry out the design of a box bridge with railings and pedestrian crossing. Which was carried out to define the final geometry of four bridge boxes distributed along the span of the 20m section with a geometry of 4.50m long each, obtaining wall and slab thicknesses of 0.35 meters with a total height of 2.50 meters. remaining 0.50m free inside each box from the maximum level of water reached. The dimensions of the wings of the bridge box are 3.30m with an angle of 140° with respect to the slab and have a diaphragm height of 2.15m and a thickness of 0.35m with a footing of 0.35 thickness, abutment tip of 0.50m and length of the 0.80m heel. With this, it will be possible to solve the vehicular flow and access to the community in all seasons of the year.